The Impact Of Ladongi Dam Construction On The Productivity Of Wet-Rice Farming In East Kolaka District - I Wayan Yogayana Saputra; Marsuki Iswandi; La Ode Alwi (International Journal of Technology and Education Research, 2024)
The research aims to determine the differences in productivity of rice paddy farms that obtain irrigation water from Ladongi Dam and rice paddy farms that do not obtain irrigation from Ladongi Dam. And to determine the income of paddy rice farms that obtain irrigation from Ladongi Dam and paddy rice farms that obtain irrigation not from Ladongi Dam. Location selection was done purposively with sampling technique purposive random sampling. The population was divided into two, namely rice paddy farms using irrigation of Ladongi Dam and rice paddy farms that do not use irrigation of Ladongi Dam. The observed variables include, respondent characteristics, namely age, education level and number of family members and farming experience. While the characteristics of farming, namely the area of cultivated land, the use of seeds, the use of fertilizers, pesticides, labor, production costs, production revenue and income. Data analysis used to determine the impact is to use the t test analysis. The results showed that the average productivity of paddy rice farming with irrigation from Ladongi Dam is equal to and which is not using Ladongi Dam irrigation of quintals per hectare. Rice paddy farming income irrigation from Ladongi Dam amounted to Rp. 14,833,483 per hectare and which is not using Ladongi Dam irrigation amounted to Rp. 12,092,541 per hectare. The results of statistical analysis of the impact of the construction of Ladongi Dam by using the analysis of differences in productivity of paddy rice farming Ladongi Dam development significantly different at 95% confidence. The impact of development affects the productivity of paddy rice in East Kolaka. The average productivity of paddy rice farming productivity that obtained irrigation from Ladongi Dam was 5,075 kilograms per hectare and not from Ladongi Dam was 4,806 kilo grams per hectare. So there is a difference in the productivity of rice paddy farming of about 269 kilograms per hectare.